SELEKSI INDIVIDU TERPILIH KEDELAI (Glycine max L.) HASIL RADIASI SINAR GAMMA GENERASI M7 - Febri Diana Lisa Saragi; Eva Sartini Bayu; E. Harso Kardhinata (Jurnal Agroekoteknologi, 2013)
The objective of this research was to obtain the high production of soybean varieties. The research conducted at Tanjung Slamat, Medan, North Sumatra (+ 25 m above sea level) in April 2012- July 2012. The research using Randomized Block Design, that is Argomulyo variety population, Anjasmoro variety population, M7. 10 krad population, M7.15 krad population and M7.20 krad. Data were analyzed by ANOVA and if there is a significantly difference was continued with Least Significant Difference test. The results showed that mutant population were significantly different to number of branches on main stem,  the number of books per plant, flowering age, harvesting age, number of empty pods per plant,  number of seeds per plant and weight of seeds per plant. From progeny test, production per plot was increased from M6 generation (195,90 g) to the M7 generation (361,33g). The high value of genetic progress was in number of empty pods per plant contains (27,2%) while the low value of genetic progress was in weight of 100 seeds. High heritability value was in flowering age (0.78) and harvesting age (0,99) while the low heritability value was in percentage of germination (0.18), number of filled pods per plant (0,19) and weight of 100 seeds (0). Keyword: soybean, irradiation, heritability, progress genetic